STUDI LITERATUR: PERBANDINGAN KINERJA CAMPURAN ASPAL RECLAIMED ASPHALT PAVEMENT DENGAN PENAMBAHAN OLI, MINYAK, DAN PLASTIK - Felix Zebua; Ismael Tafonao; Sudarno P Tampubolon; Efendy Tambunan (UKI Press, 2025)
This study is a literature review that compares the performance of recycled asphalt mixture or Reclaimed Asphalt Pavement (RAP) modified with three types of waste materials, namely waste oil, used cooking oil (WCO), and styrofoam plastic waste. An analysis was conducted on 13 scientific journals that discussed the influence of the three materials on technical parameters such as Marshall stability, flow, Marshall Quotient (MQ), and mixed durability. The results of the study show that used cooking oil (WCO) is the most optimal and environmentally friendly feedstock, as it is able to significantly increase the flexibility and durability of the RAP mixture at the ideal level of 3–6%. Used oil is also effective in restoring the aging properties of asphalt, but its use in excess amounts (>10%) can reduce its stability and resistance to water, and requires special handling because it is classified as B3 waste. Meanwhile, plastic waste such as styrofoam, PET, and LDPE are more suitable as additives to improve the structure and reduce the porosity of the mixture, although it does not function as the main contaminant. Of all the types of cooking materials used, used cooking oil (WCO) shows the most consistent performance according to Bina Marga 2010 specifications. Keywords: RAP, used oil, used cooking oil (WCO), styrofoam plastic waste